(untitled) (Baghdad Science Journal, 2020)
A spectrophotometric- reverse flow injection analysis (rFIA) method has been proposed for the determination of Nitrazepam (NIT) in pure and pharmaceutical preparations. The method is based upon the coupling reaction of NIT with a new reagent O-Coumaric acid (OCA) in the presence of sodium periodate in an aqueous solution. The blue color product was measured at 632 nm. The variation (chemical and physical parameters) related with reverse flow system were estimated. The linearity was over the range 15 - 450 µg/mL of NIT with detection limits and limit of quantification of 3.425 and 11.417 µg mL-1 NIT,respectively. The sample throughput of 28 samples per hour was achieved. Suggested method was successfully applied for the determination of NIT in its dosage forms.